45 and Up COVID Insights: a dynamic and collaborative approach to evidence-making during the COVID-19 pandemic - Greer Dawson; Kerrin Bleicher; Sarah Baynes |; Catherine D'Este; Julia Steinberg; Marianne F Weber; Jill Newby; Ding Ding; Bette Liu; Barry Edwards; Andrew Milat |; Martin McNamara (Public Health Research & Practice, 2022)
Objectives: In response to the coronavirus 2019 (COVID-19) pandemic, a research project was developed with a cohort of 45 and Up Study participants to generate timely, relevant evidence to guide policy, practice and planning. This paper describes the research model, the cohort establishment and characteristics, and some findings.